SISTEM PENUNJANG KEPUTUSAN DIAGNOSA PENYAKIT ISPA DENGAN METODE NAIVE BAYES - Halim, Emilia (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The purpose of this research is to facilitate the user to diagnose diseases of acute respiratory infections (ARI). Decision support systems have many methods that can be used by decision makers. One method is naive Bayes methods will help decision makers to make the diagnosis by filling the existing criteria. This final project will implement decision support systems with multiple criteria decision-making methods Naive Bayes for diagnosis of acute respiratory infections (ARI).